Developing CEFR-Based Digital Literacy Resources for Multisensory English Learning - Alfiani, Dewina; Khomarudin, Khomarudin (Universitas Islam Negeri Raden Intan Lampung, 2024)
Indonesia has the latest curriculum, namely the independent curriculum, whose learning is holistic and based on the CEFR level. However, in practice, the learning and teaching still uses traditional pedagogy that relies on the left brain and focuses only on grammar (linguistics). This fact is supported by evidence of a decline in the English proficiency index (EPI) in 2022 which shows that Indonesia is at a low level (ranked 81 out of 111 countries). In his latest research, Sudimantara (2021) develops a new pedagogy (Multisensorial Load Reduction Strategies) that activates the nonverbal components of language (rhythm, intonation, movement, emotion, and aesthetics). Another research by A,-P Lian & Cai (2021) also introduces a Verbotonal Approach which emphasizes prosodic information (intonation and rhythm) to rearrange the learner’s perception of the language being learned thereby facilitating language learning. In line with previous research, this research provides an innovative development of digital literacy resources for multisensory English learning based on CEFR. This research uses qualitative development with R&D (Research and Development) design with the research step to be carried out (Analyzing, design, developing, and Evaluation). The results show that these digital literacy resources can be applied by teachers for student learning. This research is expected that digital literacy can be further developed for multisensory learning which is beneficial for language learning.Keywords: CEFR-Based Learning, Digital Resources, Multisensory